The Impact of Culture, Procedure and Process of Quality Through Quality Control Towards Product Quality (Jurnal Manajemen Bisnis, 2022)
This research aims to test and analyze the influence of quality culture, quality procedures, production processes on the quality of silk cloth production in South sulawesi province and test and analyze the influence of quality culture, quality procedures, production processes on product quality through quality control of silk fabrics in South Sulawesi. Quantitative Research approach, by using survey and questionnaire methods to dig up information related to activities, where 200 as respondent, by analysis method using statistical equation model (SEM). The results showed that quality culture has a positive effect not to be denied to the quality of products, and the production process has a positive effect on product quality and quality procedures have a positive and significant effect on product quality through quality control. While Quality Culture has a significant positive effect on quality control, and production processes have a significant positive effect on quality control